The fallacy of generics in the UK - de Chernatony, Leslie (Cranfield University, 1988)
By clarifying what is meant by brands, own labels and generics this paper shows that neo-generics, rather than generics, were launched in the UK. It clarifies that neogenerics are in a terminal stage and through an understanding of consumers’ perceptions explains why this has occurred. The advent of true generics in the UK is described and the transition from neo-generics to own labels abroad is noted.